Emotional Disturbances and Resilience in Late Teens With a Broken Home Background in The Indonesian Community Emergency Broken Home (IDBH) - Anastasia Christanti; Stefanus Andang Ides; Jesika Pasaribu (Healthy-Mu Journal, 2023)
Emotional disturbances are disorders that are often characterized by irritable, anxious, and fearful behaviors. This study aims to determine the picture of emotional disorders and resilience in late adolescents with broken homes in the Indonesian Emergency Broken Home (IDBH) community. This research is of qualitative type with a descriptive qualitative method involving 8 informants. The data collection method uses a questionnaire and interview process using interview guidelines. The data analysis method carried out in this study is the colaizzi method with steps including understanding and inferring the meaning of each question item, as well as re-analyzing and making the final description results. The results obtained are that late childhood experiences changes in irritable behavior, decreased self-confidence and. The act of self-harm, there are varied ways that adolescents have in increasing resilience by doing positive things such as hobby development, self-acceptance and emotional control